Local super apps in the 15-minute city: a new model for sustainable smart cities? - Marc Hasselwander; Daniel Weiss; Stefan Werland (Frontiers in Sustainable Cities, 2024)
In this perspective paper, we propose to integrate the concepts of Mobility-as-a-Feature (MaaF, an extension of MaaS) and the 15-minute city (15mC). The 15mC concept maintains that daily necessities and services, such as shopping, healthcare, and leisure should be accessible without private cars within 15 minute. In line with MaaF, these services could be integrated with a variety of mobility options into a single app. This novel approach is poised to offer a seamless customer experience, better resource utilization, enhanced urban mobility, improved and more inclusive access to services, and greater community connectivity. We call them local super apps: a new model to drive equitable and sustainable urban transitions. We substantiate this preliminary idea with evidence from literature, practical applications, and a user survey (N = 1,019), while also discussing future research avenues to further develop the concept of local super apps.